Compact back‐to‐back DRA‐based four‐port MIMO antenna system with bi‐directional diversity. Issue 14 (1st July 2018) - Das, G.; Sharma, A.; Gangwar, R.K.; Sharawi, M.S.
Abstract : This Letter presents a dielectric resonator (DR)‐based multiple‐input‐multiple‐output (MIMO) antenna with bi‐directional pattern diversity. The back‐to‐back arrangement of cylindrical DR antennas DRAs (cDRAs) is one of the unique features of the proposed design. The cDRAs are placed on an FR4 substrate with a common ground plane. Each cDRA element is excited by two ports to establish a four‐port MIMO antenna system. At ports 1 and 2, the top cDRA is excited via co‐planar waveguide (CPW) fed conformal strip lines. In case of ports 3 and 4, the bottom cDRA is excited by microstrip line fed conformal strip lines. Isolation between all ports is improved (better than 18 dB) by generating orthogonal modes in the cDRAs and use of opposite excitations. Measured results confirm that the proposed four‐port MIMO antenna system is useful for the frequency ranges between 5.4 and 6.0 GHz for WLAN applications.